Navigating Academic Storms: A Narrative Inquiry into Student Resilience and the Silent Power of Parental Attachment in Higher Education - Dika Sahputra; Andika Fawri; Aisyah Amini; Mansor Abu Talib (International Journal of Educational Narratives, 2026)
Background. The quality of parental closeness, characterized by trust, effective communication, and low levels of alienation, is considered a protective factor in fostering academic resilience Purpose. This study aims to analyze the determination of the quality of parental closeness on students’ academic resilience in an era of high academic pressure. Increasing academic demands, competition, and performance expectations require students to possess strong adaptive abilities in order to survive and achieve academic success. Method. This study employed a quantitative approach with a sample of 140 university students. Data were collected using a parental closeness scale and an academic resilience scale, and were analyzed using descriptive and inferential statistical techniques. Results. The results indicated that the quality of parental closeness was generally in the moderate to high category, with trust emerging as the most dominant dimension. Meanwhile, the level of students’ academic resilience was predominantly in the moderate category (56.429%), followed by the high category (37.143%), suggesting that most students have a fairly good capacity to cope with academic pressure. Conclusion. These findings indicate that the higher the quality of parental closeness, the stronger the students’ academic resilience. Supportive relationships provide a sense of security, emotional support, and psychological resources that help students manage stress and academic challenges in an adaptive manner.